Photovoice Study on EFL Students’ Blended Learning Experiences - Efrilia Siska Damayanti; misdi (Foreign Language Instruction Probe, 2025)
Blended learning is an alternative form of learning model that combines the conventional learning model (face-to-face learning) with the e-learning learning model. This study examined how students felt about their online dan face-to-face learning experiences. Five EFL students at the private university in Indonesia participate d in photovoice and interview sessions. Thematic analysis identified three themes, which are the benefits and challenges of blended learning; online and offline learning; and the future of blended learning. The use of photovoice was successful in capturing details of blended learning implementation on EFL students. The result of this study represents blended learning has many benefits for students. Two benefits, in particular, are its versatility and accessibility. The students enjoyed and felt their academic performance developed. However, an important advance needed for the implementation of blended learning is better internet access.